Unicornuate uterus with rudimentary horn, gynaecological and reproductive outcome - Anand, Arti; Chandra, Madhuri; Agarwal, Meeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Congenital malformations of the female genital tract occur in about 8-10% of all women. The unicornuate uterus is a result of partial or complete agenesis of one of the paired Mullerian ducts. It could be a true unicornuate uterus or along with a rudimentary horn, which may be functional. When the rudimentary functional horn is non-communicating, most patients become symptomatic after menarche or present with pregnancy related problems. Three clinical presentations of unicornuate uterus with non-communicating rudimentary horn encountered in last one year are described. The first case was of unruptured rudimentary horn pregnancy of 11-12 weeks. Second case had rudimentary horn removed as an adolescent due to intractable pain, but later main uterus harboured an uneventful pregnancy. Case three had two early abortions, followed by term caesarean section for fetal distress. With advent of ultrasonography and other imaging techniques, the diagnosis and management of unicornuate uterus and its variations is possible. The functional rudimentary horn if symptomatic must be removed along with ipsilateral tube. A unicornuate uterus is associated with obstetric problems and such women should be considered as high risk pregnancy.